2016
DOI: 10.1111/papr.12484
|View full text |Cite
|
Sign up to set email alerts
|

Nervous System Sensitization as a Predictor of Outcome in the Treatment of Peripheral Musculoskeletal Conditions: A Systematic Review

Abstract: This systematic review found insufficient evidence to support an independent predictive relationship between QST measures of nervous system sensitization and treatment outcome. Self-report measures demonstrated better predictive ability. Further high-quality prognostic research is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 76 publications
1
42
0
Order By: Relevance
“…However, current results are also contrary to those previously observed in subjects with whiplash‐associated disorders, where patients exhibiting augmented central pain processing obtained worse clinical outcomes than those patients exhibiting localized mechanical hyperalgesia after participating in an exercise treatment program . In addition, the lack of a prognostic role of central sensitization is also contrary to what is seen in musculoskeletal pain conditions . It is possible that the role of central sensitization in neuropathic conditions would be different than in musculoskeletal pain conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, current results are also contrary to those previously observed in subjects with whiplash‐associated disorders, where patients exhibiting augmented central pain processing obtained worse clinical outcomes than those patients exhibiting localized mechanical hyperalgesia after participating in an exercise treatment program . In addition, the lack of a prognostic role of central sensitization is also contrary to what is seen in musculoskeletal pain conditions . It is possible that the role of central sensitization in neuropathic conditions would be different than in musculoskeletal pain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Most trials investigating prognostic factors of outcomes following conservative treatments have focused on local treatments such as corticosteroid injections . A recent review found preliminary evidence suggesting that central sensitization in musculoskeletal pain conditions is associated with poorer outcomes in response to either surgical or conservative treatment . Although there is evidence supporting the presence of central sensitization in CTS, studies addressing the relationship between sensitization and treatment outcomes are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…PMPs of test procedures are specific to test sites and study populations . In PJP populations particularly, only 1 systematic review has surveyed the existing evidence of predictive validity of different QST procedures . This systematic review found that only cold pain threshold assessed using the thermotest system (Somedic AB, Frasta, Sweden) predicts pain and disability 1 year later in individuals with chronic lateral epicondylitis .…”
Section: Introductionmentioning
confidence: 99%
“…Background: Ultrasonography can detect subclinical changes in anterior chest wall (ACW) joints of patients with ankylosing spondylitis (AS). 1 Pulmonary functions may be affected during the course of AS. 2 Up to the best of our knowledge, there are no previous studies of the relationship between ultrasound detected subclinical changes in ACW and the pulmonary functions in AS patients.…”
mentioning
confidence: 99%